2010
DOI: 10.1080/09640568.2010.490058
|View full text |Cite
|
Sign up to set email alerts
|

Does intensity of change matter? Factors affecting adoption of agri-environmental schemes in Spain

Abstract: Agri-environmental schemes (AES) are the main policy instrument currently available in the EU to promote environmentally-friendly farming practices. However, the rate of adoption of these measures is still relatively low in southern Europe, and understanding how these rates can be increased is still an open issue. The goal of this paper is to increase that understanding by testing whether the factors which determine AES sign-up decisions are influenced by the intensity of change in farming practices that are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 16 publications
6
62
1
1
Order By: Relevance
“…Defrancesco et al (2008), Barreiro-Hurle et al (2010) and Mathijs (2003) each found that when farm income is a high proportion of total household income, this has a negative impact on the farmers' willingness to participate in an AES. This variable also was included by Ruto and Garrod (2009) when studying farmers' willingness to sign up for short or long-term AES contracts.…”
Section: Economic Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…Defrancesco et al (2008), Barreiro-Hurle et al (2010) and Mathijs (2003) each found that when farm income is a high proportion of total household income, this has a negative impact on the farmers' willingness to participate in an AES. This variable also was included by Ruto and Garrod (2009) when studying farmers' willingness to sign up for short or long-term AES contracts.…”
Section: Economic Factorsmentioning
confidence: 95%
“…They explained this result by pointing to the age of the sample of non-adopters, who tended to be younger than those farmers characterised as active participants in AES. Defrancesco et al (2008) and Barreiro-Hurle et al (2010) associated the likelihood of enrolment with the farming practices required for partipation in an AES, which in their cases were similar to those applied in more traditional low intensity farming systems and therefore more familiar to older farmers as well as being relatively easy to implement. The findings of Polman and Slangen (2008) and Peerlings and Polman (2009) did not support this conclusion.…”
Section: Farmer's Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Some researchers, for example, have demonstrated that younger farmers are more likely than older farmers to participate in agri-environmental initiatives (Wynn et al, 2001;Murphy et al, 2011) and adopt new technologies (D'Souza et al, 1993). Other studies have found evidence for the opposite trend (Hoover and Wiitala, 1980;Abd-Ella et al, 1981;Lasley and Nolan, 1981;Barreiro-Hurlé et al, 2010) as well as for no relationship either way between age and adoption of conservation practices (Carlson et al, 1981;Wilson, 1997;Finger and Lehmann, 2012).…”
mentioning
confidence: 99%
“…shown, for example, to enhance the adoption of organic farming (Best, 2009), participation in agri-environmental schemes (Lambert et al, 2007;Barreiro-Hurlé et al, 2010), and investment in sustainability measures (Jay, 2005). Yet again, other studies found no or an inverse relationship between the degree of education and environmental behavior in farmers (see Burton, 2014).…”
mentioning
confidence: 99%